An analysis of the bacteria produced in pressure ulcers and the costs of antibiotherapy for patients in a long-term intensive care unit (Annals of Medical Research, 2021)
Aim: The aim of this study was to examine the bacteria produced patients with pressure ulcers (PU) in Long-term intensive care unit (LTICU) and to evaluate the costs of antibiotherapy.